An investigation into the conceptual metaphors expressing happiness, sadness, fear, and anger in poems and short stories in English and Vietnamese - Nguyễn Văn Ba (The University of Da Nang, 2014)
Introduction; Literature review and theoretical background; Methods and procedures; ...